(untitled) (Per Musi, 2021)
This article describes the musical and cognitive results achieved with a student on the Autism spectrum, as part of a doctoral research (2013-2017) carried out in the Department of Neurology-Neurosciences at UNIFESP. The student was eleven years old and had 40 hours total of classes, over a period of 4 months. The classes happened twice a week, and were 80 minutes in length. Class activities included pedagogically based music games with a focus on sound properties and physical movement. The main theoreticalfoundations were Pacheco (2009), Mateiro and Ilari (2011), Fonseca (2010) and Lent (2010). The results pointed the knowledge retention of music content based on the properties of sound, as well as significant improvement in cognitive skills and self-awareness related to the student’s body image-scheme. This report can contribute both to the body of knowledge of music educators with students on the Autism Spectrum, and health professionals.